Chinese Muslim at Political Crossroad: The Case Study of the Jakarta Regional Head Election 2017 - Wirman, Hardi Putra; Burhanuddin, Nunu; Elvira, Maiza (Islam Realitas: Journal of Islamic and Social Studies, 2022)
As ethnic minorities who adhere to the majority belief (Islam), ethnic Chinese Muslims in Jakarta are faced with a complex identity crisis, especially in the area of political participation. In the 2017 Jakarta regional elections (Pilkada), ethnic Chinese Muslims were faced with a political situation, whether to choose leaders from ethnic Chinese or leaders from the Muslim community. This situation puts them in a dilemma. However, ethnic Chinese Muslims have survived the complicated politics of ethnicity, even though regional election politics has caused a crisis of identity politics in Jakarta. Based on the research results, Chinese Muslims in Jakarta were able to survive despite the difficulties caused by their identity. This research is important because there are not many studies that specifically discuss the survival strategies of Chinese Muslims in Jakarta. This research is a socio-political research. To collect data, the methodology used is in-depth interviews with several informants. The results of the interviews and data are then processed using a qualitative and analytic approach. This is done in order to show how the Chinese Muslim ethnic group have survived the complicated political situation in Jakarta